Impact of Wind‐Wave Coupling on Turbulence and Air‐Sea Fluxes: Insights From Direct Numerical Simulations - Jinlong Zhang; Weijian Liu; Yuhong Dong (Geophysical Research Letters)
Abstract Accurate prediction of air‐sea fluxes hinges on a deep understanding of wind‐wave interactions, yet feedback mechanisms involving surface waves and wind are not fully understood. This paper investigates the effect of two‐way coupling between wind and waves on wind turbulence through direct numerical simulation of air‐water two‐phase flows, with simulations of non‐coupling cases for wind sea and swell. Compared to the uncoupled model, the dissipation of surface waves absorbs momentum from the wind for a wind sea, reducing turbulence intensity, which decreases momentum and heat transfer coefficients (CD and CH). In a swell scenario, a wave‐driven wind jet produces strong shear and changes interfacial dynamics under coupled conditions, enhancing turbulence intensity within the wave boundary layer. Air‐water interaction fosters a positive feedback loop between wind and swells, leading to a consequent increase in CD and CH. Parameterizations of CD and CH need to account for the wind‐wave coupling.